A temperature responsive hydrogel encapsulated with adipose‐derived stem cells and melanin promotes repair and regeneration of endometrial injury - Ruigao Song; Chicheng Ma; Hongxia Li; Yu Cheng; Xianmei Cui; Zanhong Wang; Lijuan Huang; Chunying Song; Yukai Jing; Bing Cao; Lili Wang; Qing Tian; et al. (Bioengineering & Translational Medicine)
Abstract The endometrium, the inner lining of the uterus, assumes a crucial role in the female reproductive system. Disorders and injuries impacting the endometrium can lead to profound consequences, including infertility and compromised women's overall health. Recent advancements in stem cell research have opened new possibilities for the treatment and repair of endometrial issues. In the present study, we constructed a degradable hydrogel by loading adipose‐derived stem cells (ADSCs) and melanin nanoparticles (MNP). In vitro cell experiments validated the biocompatibility of the prepared hydrogels and their adeptness in encapsulating ADSCs. Subsequently, we explored the impact of hydrogel@ADSC@MNP constructs in the healing process of uterine injury in mice. The results indicated that hydrogel@ADSC@MNP could augment endometrial thickness and ameliorate endometrial interstitial fibrosis. The injured tissue adjacent to hydrogel@ADSC@MNP constructs exhibited higher levels of bFGF, IGF‐1, and VEGFA compared with the corresponding tissue in mice receiving hydrogel constructs alone or in the model group. Furthermore, the hydrogel@ADSC@MNP system enhanced the proliferative capabilities of uterine endometrial cells, facilitated microvasculature regeneration, and reinstated the endometrium's capacity to receive the embryos. Our findings strongly suggest that the hydrogel@ADSC@MNP system holds significant promise for repairing and regenerating damaged endometrium.